Peran Lembaga Muhammadiyah dalam Mitigasi Bencana di Kabupaten Sinjai - Kiki Rasmala Sani; Syamsuddin Syamsuddin (JURNAL SOSIAL HUMANIORA (JSH), 2020)
This study aims to analyze the role of the Muhammadiyah Institute in disaster mitigation in Sinjai region. As a large organization in Sinjai, Muhammadiyah serves as the government’s partner in promoting disaster preparedness to the public via institutions that were founded on the level of Regional Leadership and the level of business charity. This research uses descriptive analysis with qualitative methods. The respondents were Muhammadiyah Regional Leaders, Muhammadiyah Disaster Management Institutions, and Muhammadiyah cadres in the Sinjai region. The results of this study indicated that the institution, since the Regional Leadership of Muhammadiyah Sinjai founded it, had not had a work program. Thus, the agency has not yet significantly contributed to disaster mitigation. All cadres who exist in the structure of the institution are cadres in various other organizations that can be resources in achieving organizational goals